The Effect of Product Quality and Promotion on Purchase Decisions with Brand Image as an Intervening Variable (Case Study on Tupperware Product Users in Padang City) - Windy Kusumahati; Rahmad Taklim; Riko Erlima Putra; Fesaraweny Fesaraweny; Habibah Muharmi; Rozi Destian (Jurnal Multidisiplin Sahombu, 2026)
This study aims to examine the influence of product quality and promotion on purchasing decisions with brand image as an intervening variable (a case study of Tupperware product users in Padang City). Data collection methods include surveys and questionnaires, with a sample of 100 respondents. The analysis method used is path analysis using SPSS. The research results show that product quality and promotion have a positive and significant effect on brand image. Product quality, promotion, and brand image have a positive and significant effect on purchasing decisions. Brand image mediates the relationship between product quality and purchasing decisions. Brand image mediates the relationship between promotion and purchasing decisions. The contribution of the independent variables Product Quality and Promotion to the dependent variable Brand Image is 49.9%. The remaining 51.1% is influenced by other variables outside this study. The contribution of the independent variables Product Quality, Promotion, and Brand Image to the dependent variable Purchase Decision is 24.0%. The remaining 74.4% is influenced by other variables outside this study.